A histological and radiographic study of pulpal calcification in periodontally involved teeth in a Taiwanese population - Liang-Gie Huang; Gin Chen (Elsevier, 2016)
Background/purpose: The prevalence of pulpal calcifications was widely studied in the past. The purposes of this study were to investigate the incidence of pulpal calcifications of periodontally involved teeth in a Taiwan Chinese population using radiographic and histological examinations, and to find out any association of pulpal calcification with systemic disease and dental conditions. Materials and methods: A total of 197 teeth freshly extracted because of severe periodontal destruction were collected and prepared for histological and radiographic studies of the incidence of pulpal tissue calcifications. The occurrences of calcifications were recorded based on the different types of classifications proposed by Seltzer (1972). The number of examined teeth with pulpal calcifications was calculated, and they were statistically analyzed with the Chi-square test. Results: The patient population ranged in age from 16 years to 85 years. Of them, 165 (84%) were male and 32 (17%) were female. The results show that the incidence of pulpal calcifications of periodontally involved teeth was 62% in histological and 30% in radiographic examinations. The occurrences were slightly higher than that reported in some previous studies and significantly different between the two examined methods. No significant association of pulpal calcification with age and systemic disease was found. Moreover, molars were observed to have more pulpal calcifications than bicuspids and incisors statistically (P<0.001). Conclusion: The true incidence of pulpal calcifications of periodontally involved teeth is likely to be higher in histological examination because pulpal calcifications with a small diameter may not be seen on radiographs. The prevalence of pulpal calcifications was found to increase significantly in molar teeth, and the results indicated that localized calcifications occur mostly in the radicular area of the pulp tissue.